Water quality modeling in bērze river catchment - Kaspars Abramenko; Ainis Lagzdiņš; Artūrs Veinbergs (Journal of Environmental Engineering and Landscape Management, 2013)
The paper describes water quality modeling approaches for the mid-sized river (1001000 km2) catchment in Latvia. The hydro-chemical data (2005 to 2010) in 15 subcatchments of Bērze River (872 km2) represent water quality and land use type-specific concentrations. Water sampling shows that significant pollution results from management of organic manure and intensive agriculture, where the maximum concentrations of nitrate nitrogen are 9.2 and 18.1 mg l−1 reaching or exceeding the limit established by the EU Nitrates Directive of 11.3 mg l−1. The application of pollution load source apportionment could be useful for decision making to set up the action plans for the implementation of appropriate pollution reduction measures.